New record of Phaeocollybia jennyae in Spain - Bandala Muñoz, Víctor M.; Montoya Bello, Leticia; Rocabruna i Llavanera, August (Revista Catalana de Micologia, 2004)
Phaeocollybia jennyae (Cortinariaceae, Basidiomycetes) was found in Spain growing in a Fagus sylvatica forest in Catalonia. The species is known to inhabit northern Europe, but it don’t had been recorded fi-om Spain yet. A description and illustrations of the catalan material is presented. The type collection from Finnland, as well as two samples collected by P. Karsten, were also studied. The microscopic observations on these collections are included.